2007
DOI: 10.1016/j.adolescence.2007.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Over‐connected? A qualitative exploration of the relationship between Australian youth and their mobile phones

Abstract: In Australia, youth are the most prolific users of mobile phones, however, there is little research investigating this phenomenon. This paper reports a qualitative exploration of psychological factors relating to mobile phone use amongst Australian youth. 32 participants, aged between 16 and 24 years, took part in focus group discussions. Thematic data analysis focussed on identifying the psychological benefits arising from mobile phone use and whether mobile phone addiction was occurring amongst this group. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
192
0
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(211 citation statements)
references
References 25 publications
(28 reference statements)
9
192
0
10
Order By: Relevance
“…4 We would argue, however, that more research is needed before the MPPU can be considered as a diagnostic category, even though some authors 11 do regard it as a clinical entity. To conclude, the use of mobile phones seems to be an intrinsic part of young people's lives, one that is reinforced through the self-and social gratification it provides, 41,42 and which also enables young people to manage their own emotions and behavior. 20,22,24 Given the current availability of Internet-enabled mobile phones as tools for communication and entertainment among adolescents, research is needed that addresses the use of these smartphones, which may lead to more use overall, 43 as well as to addictive behaviors that can be associated with problematic use.…”
Section: Discussionmentioning
confidence: 99%
“…4 We would argue, however, that more research is needed before the MPPU can be considered as a diagnostic category, even though some authors 11 do regard it as a clinical entity. To conclude, the use of mobile phones seems to be an intrinsic part of young people's lives, one that is reinforced through the self-and social gratification it provides, 41,42 and which also enables young people to manage their own emotions and behavior. 20,22,24 Given the current availability of Internet-enabled mobile phones as tools for communication and entertainment among adolescents, research is needed that addresses the use of these smartphones, which may lead to more use overall, 43 as well as to addictive behaviors that can be associated with problematic use.…”
Section: Discussionmentioning
confidence: 99%
“…For example, only 10% of bullying studies reported between 2000 and 2004 utilised a qualitative methodology (Powell et al, 2008), Consequently, to develop a much broader, and deeper approach surrounding the issues generated within the school context and to consider more implicitly the issues and questions raised, this empirical groundwork utilised an interpretive approach (Walsh, White, and Young, 2008). This was an attempt to understand the very personal perceptions of bullying experiences (Torrance, 2000) between teacher and parent.…”
Section: Methodsmentioning
confidence: 99%
“…Each interview was initially manually interrogated and coded initially using the Acrobat software according to sub-themes that 'surfaced' from the interview dialogue -using a form of open-coding derived from Glaser (1992a);and Straus and Corbin (1990). This treatment was also reinforced and extended through the use of thematic analysis conducted using the NVivo 9 -qualitative software package (Walsh, White and Young, 2008). Each interview was treated and coded independently.…”
Section: Methodsmentioning
confidence: 99%
“…13 Young female adolescents and parents report increased feelings of security as a result of cell phones. 14,15 Some research suggests that merely owning, and not actually using, a cell phone helped adolescents to feel socially connected. 16 The purpose of this study was to conduct a preliminary examination of cell phone ownership and use among a sample of homeless youth, particularly the social and instrumental uses of cell phones which have implications for health outcomes.…”
Section: Introductionmentioning
confidence: 99%